PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TEKNIK STAD (STUDENT TEAM ACHIEVMENT DIVISIONS) UNTUK MENINGKATKAN LONG FOREHAND SERVICE PERMAINAN BULU TANGKIS (JURNAL ILMU KEOLAHRAGAAN, 2024)
This research aims to improve forehand serviceability using the STAD Student Team Achievement Division cooperative model). This research uses a quantitative approach with a pre-experimental design. The sample involved in this research is all students at SDN Babakan Bandung who take part in badminton extracurriculars. The research sample selection technique used was a total sampling of 18 people. Total sampling means the number of samples is the same as the population. The data collection technique used in this research is a test. The test carried out was a performance test of Nurhasan's long forehand service badminton ability. The data analysis test used the t-test with results showing a value of 0.01 < 0.05, which shows that the STAD learning model can improve long forehand serve ability in badminton. The normality statistical test uses Kolmogorov Smirnov with normal distribution results. Data from the t-test results with results of 0.001 < 0.05. So, there is a significant influence. The results of this test shown in R Square are 0.660, which means that the STAD learning model has a large influence of 66% on the long serve forehand in badminton.